TINJAUAN KOREOGRAFI TARI MAPAK DI TEBING TINGGI KABUPATEN EMPAT LAWANG SUMATERA SELATAN - Wulan Permata Sari; Desfiarni Desfiarni; Afifah Asriati (FBS Universitas Negeri Padang, 2014)
ABSTRACT This article aimed at describing the choreography of the Mapak dance at Tebing Tinggi Kabupaten Empat Lawang Sumatera Selatan. The design of this research was descriptive qualitative research. Data were obtained from the library study, observantion, and interview. From the data analysis, it was found that the Mapak dance was performed as a welcoming dance for important guests who came to Kabupaten Empat Lawang and a veil was given to the guests at the end of the dance. There were six kinds of move included in this dance. They were the meaningful movements which included the entrance moves, the greeting moves, and the inviting moves and the pure movements which included the ngunjak moves, the honoring moves and the resting move. The flooring design dominantly used the straight line. The top designs included the deep, angular, conceited, medium and low designs. The accompaniment music was the external music. The one climax dramatic design used was the singular cone. The big group was composed by using the united and the equilibrate designs. The costumes worn for dancing were baju kurung, songket, and its accessories. The makeup used beautiful. The theme of the activity was welcoming the guests and the dance was performed at an open yard. Keywords : Choreography, the Mapak dance at Tebing Tinggi Kabupaten Empat Lawang Sumatera Selatan